The Effect of Using Elastic Lumbar Corset on Fatigue on Lifting Employee - Anggriani, Atika Febri; Fathi, Muhamamd; Luhuri, Rendy; Utomo, Prasetyo Catur (Journal of Prosthetics Orthotics and Science Technology, 2023)
Background: In everyday life, human beings cannot be separated from lifting activities, which can lead to fatigue. Lumbar corset can keep the body in an upright position thereby reducing fatigue.Research objectives: To find out an effect of using elastic lumbar corset on fatigue levels in lifting employee at PT Budi Texindo, Jawilan District, Serang Regency, Banten. Method: This study is quasi-experimental quantitative research using SSRT measuring instruments with a total of 20 respodents with a pre-posttest method, the normality test is using Shapiro-wilk and a hypothesis test using a paired T test. Research results: This research shows the average fatigue in the pretest group (59.50) while the average fatigue in the post test group (54.10), with a difference (5.40). Test results statistics with Paired t-test showed a p value of 0.000 it means <0.05 so there is a significant effect of using elastic lumbar corset on fatigue level.Conclusion: There is an effect of using Elastic Lumbar Corset on the fatigue level of lifting employees.